2015
DOI: 10.1016/j.ijrobp.2015.07.1182
|View full text |Cite
|
Sign up to set email alerts
|

c-Met Overexpression in Cervical Cancer: A Prognostic Factor and a Potential Molecular Therapeutic Target

Abstract: Purpose-This study aimed to assess the association between pretreatment c-Met overexpression in local-regional advanced cervical cancer patients treated definitively with concurrent chemoradiation (CRT) and treatment outcomes including overall survival (OS), progression free survival (PFS), distant metastases control (DM), and local-regional control (LC).Patients and Methods-This IRB approved study included cervical cancer patients treated definitively and consecutively with CRT. Evaluation of cytoplasmic immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Upregulation of EGFR has been reported in cervical cancers; it contributes to cancer cell proliferation, migration, and invasion. Another highly expressed proto-oncogene in cervical cancer is c-MET (12), which is known to promote the occurrence and development of cervical cancer and has prognostic value (13). Given the fact that cervical carcinomas are caused by persistent HR HPVs infection, elevated proto-oncogene expression is also possibly a consequence of the HR HPVs infection (14).…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of EGFR has been reported in cervical cancers; it contributes to cancer cell proliferation, migration, and invasion. Another highly expressed proto-oncogene in cervical cancer is c-MET (12), which is known to promote the occurrence and development of cervical cancer and has prognostic value (13). Given the fact that cervical carcinomas are caused by persistent HR HPVs infection, elevated proto-oncogene expression is also possibly a consequence of the HR HPVs infection (14).…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggest that the negative relationship between c‐MET expression and cervical cancer prognosis may be due to the increased cell response to HGF that could in turn induce tumor cell metastasis (Baykal, Ayhan, Al, Yuce, & Ayhan, ). Refaat et al also suggest that the overexpression of c‐Met may be a potential therapeutic target, with a predictive value for subjects with local‐regional advanced cervical cancer treated definitively with concurrent chemoradiation (Refaat et al, ). A meta‐analysis by Peng et al found that c‐Met expression in cervical cancer was approximately 60.99% (222/364), and the c‐Met expression was higher in this malignancy rather than non‐neoplastic cervix tissue.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of evidence has proven that c-Met is upregulated in several cancer types, including gastric ( 15 ), non-small-cell lung ( 16 ) and cervical cancer ( 17 ). In addition, previous studies demonstrated that overexpression of c-Met has as a significant prognostic value in early-stage invasive ( 18 ) and local-regional advanced cervical cancer patients ( 19 ). c-Met, acts as an oncogene, and has been widely documented to promote cell proliferation, migration and invasiveness ( 20 ).…”
Section: Discussionmentioning
confidence: 99%